Dancing in the Distraction Factory / Music Television and Popular Culture - Goodwin Andrew (Rouledge, 1993)
Acknowledgements, Author's Note, Introduction, Silence! Academics at Work, From Anarchy to Chromakey Developments in Music Television, A Musicology of the Image, The Structure of Music Video Rethinking Narrative Analysis, Metanarratives of Stardom and Identity, A Televisual Context: MTV, Aesthetics and Politics in Music Television Postmodernism Reconsidered, Concluding Thoughts, Music Television Time Line, Notes, Bibliography, Index.
Acknowledgements, Author's Note, Introduction, Silence! Academics at Work, From Anarchy to Chromakey Developments in Music Television, A Musicology of the Image, The Structure of Music Video Rethinking Narrative Analysis, Metanarratives of Stardom and Identity, A Televisual Context: MTV, Aesthetics and Politics in Music Television Postmodernism Reconsidered, Concluding Thoughts, Music Television Time Line, Notes, Bibliography, Index.